Local inflammatory marker production in Lithuanian patients with chronic rhinosinusitis with nasal polyps. Issue 1 (1st January 2020) - Vaitkus, Justinas; Vitkauskiene, Astra; Matuseviciute, Vilte; Naudziunas, Albinas; Siupsinskiene, Nora; Vaitkus, Saulius
Abstract: There are two clinical subtypes of chronic rhinosinusitis (CRS): chronic rhinosinusitis with nasal polyps (CRSwNP) and chronic rhinosinusitis without nasal polyps (CRSsNP). The aim of the study here was to determine the levels of invasive inflammatory markers in nasal mucosa samples taken from CRSwNP patients during the surgery and to identify markers that could serve as targets for potential clinical and therapeutic interventions. The study was carried out in 59 patients with proven CRSwNP and a control group consisting of 52 healthy individuals. Concentrations of the inflammatory markers of interest were determined using a LuminexR Assay multiplex kit. The data obtained indicated that levels of inflammatory cytokines interleukin (IL)-2, -4, -5, -7, -12, -17 and -22 were all significantly higher in the nasal polyps (NP) than those in the mucosa of control participants. No differences were seen between the study groups for IL -6, -10, -13, -21 and interferon (IFN)-γ. OR (Odds Ratio) analyses confirmed that elevations in mucosal levels of IL-2, -4, -5, -7, -12, -17, and -22 were likely immune markers of CRSwNP. In conclusion, the present study demonstrated that IL-2, -4, -12 and -22 may be important in the etiopathogenesis of CRSwNP; as markers, each show moderate sensitivity, but high specificity in the Lithuanian population. IL-17 had good sensitivity, but low specificity in the CRSwNP patients.